Canadian consensus statement on the management of radioactive iodine–resistant differentiated thyroid cancer. (October 2021) - Boucher, Andrée; Ezzat, Shereen; Hotte, Sebastien; Rachinsky, Irina; Rajaraman, Murali; Ruether, Dean; Wiseman, Sam M.; Brierley, James; Ho, Cheryl; Krzyzanowska, Monika; Lamond, Nathan; Massicotte, Marie-Hélène; et al.
Highlights: Radioactive iodine-resistant thyroid cancer (RAIRTC) is uncommon and heterogeneous in its clinical behavior. Recognition and awareness of treatment options for RAIRTC varies widely. This document offers guidance to ensure timely and comprehensive expert RAIRTC management. Abstract: Radioactive iodine-resistant differentiated thyroid cancer (RAIRTC) is an aggressive form of thyroid cancer that is uncommon and heterogeneous in its clinical behavior. With the emergence of more effective systemic therapy, the need for guidance in decision-making was recognized and a consensus committee of national experts was assembled. The consensus committee consisted of 13 clinicians involved in treating RAIRTC from across Canada and included endocrinologists, nuclear medicine physicians, surgeons, and radiation and medical oncologists. Domains of interest were identified by consensus, and evidence gathered using systematic reviews. Consensus recommendations for the diagnosis and management of RAIRTC were developed. It was recognized that the rarity of RAIRTC in practice and heterogeneous patterns of thyroid cancer care could limit access to effective therapy for some RAIRTC patients. This document offers guidance to manage RAIRTC patients in a multidisciplinary manner.